Smart Water Filling and Bottle Handling using STM32 and IoT - BINTI RAMLEE, FARZANA NAZIRAH; BIN MUHAMMAD RAZIF, MUHAMMAD RUSYDI (Progress in Engineering Application and Technology, 2024)
Smart Water Filling and Bottle Handling project using STM32 and IoT systems aims to modernize inventory management and production line control. This system uses wireless technology to automate inventory data collection and monitoring, reducing manual data entry and human error. The primary objective is to optimize production line efficiency by maintaining adequate stock levels in a warehouse equipped with a wireless monitoring system. This will enhance the performance and reliability of the entire production line, reduce manufacturing lead time, and benefit the inventory management and manufacturing environment.